2015
DOI: 10.3892/ijo.2015.2952
|View full text |Cite
|
Sign up to set email alerts
|

The novel desmopressin analogue [V4Q5]dDAVP inhibits angiogenesis, tumour growth and metastases in vasopressin type 2 receptor-expressing breast cancer models

Abstract: Desmopressin (dDAVP) is a safe haemostatic agent with previously reported antitumour activity. It acts as a selective agonist for the V2 vasopressin membrane receptor (V2r) present on tumour cells and microvasculature. The purpose of this study was to evaluate the novel peptide derivative [V4Q5]dDAVP in V2r-expressing preclinical mouse models of breast cancer. We assessed antitumour effects of [V4Q5]dDAVP using human MCF-7 and MDA-MB-231 breast carcinoma cells, as well as the highly metastatic mouse F3II cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 49 publications
7
48
0
1
Order By: Relevance
“…Nevertheless, Zhu and Weiss [1998] found that a similar, but inherited, truncated vasopressin receptor molecule referred to the Utah mutation when coexpressed with wild-type V2 receptor dimerized with this form and effectively inhibited all downstream activity. Since we, and others [North, 2000;North et al 1998ab;Taylor et al, 1990;Ripoll et al 1990;Garona et al, 2015], have demonstrated that vasopressin action through V2 receptors is inhibitory to the growth of solid tumors, we have concluded that tumors probably manufacture AbnV2R as a null receptor to impair such growth inhibition. Since Alonso and coworkers [Ripoll et al, 2013;Garona et al,2015] have shown that activation of tumor V2 receptors seems to impair angiogenesis and tumor metastasis as well as retard growth of breast cancer, it is conceivable that all these mechanisms could also play some role in the inhibitory actions of Abner if the antibody internalizes and removes the null receptor and allows influences by tumor-generated vasopressin to be increased through normal V2 receptors.…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, Zhu and Weiss [1998] found that a similar, but inherited, truncated vasopressin receptor molecule referred to the Utah mutation when coexpressed with wild-type V2 receptor dimerized with this form and effectively inhibited all downstream activity. Since we, and others [North, 2000;North et al 1998ab;Taylor et al, 1990;Ripoll et al 1990;Garona et al, 2015], have demonstrated that vasopressin action through V2 receptors is inhibitory to the growth of solid tumors, we have concluded that tumors probably manufacture AbnV2R as a null receptor to impair such growth inhibition. Since Alonso and coworkers [Ripoll et al, 2013;Garona et al,2015] have shown that activation of tumor V2 receptors seems to impair angiogenesis and tumor metastasis as well as retard growth of breast cancer, it is conceivable that all these mechanisms could also play some role in the inhibitory actions of Abner if the antibody internalizes and removes the null receptor and allows influences by tumor-generated vasopressin to be increased through normal V2 receptors.…”
Section: Discussionmentioning
confidence: 56%
“…Cell cycle distribution. Cell cycle phase distribution and hypodiploid population quanti cation in starved OSA cells following a 24 h PPN (50 µM) treatment was evaluated by ow cytometry as previously reported [25] (for detailed methodology see Additional le 1. Supplementary methods).…”
Section: Methodsmentioning
confidence: 99%
“…Clonogenic growth. Effect of PPN (1, 10 or 50 µM) on OSA colony forming ability was assessed using a 7-d clonogenic assay, as previously reported [25] (for detailed methodology see Additional le 1.…”
Section: Methodsmentioning
confidence: 99%
“…Наряду с опухолями, тромбоциты и эндотелиоциты относятся к наименее исследованным клеточным мишеням вазопрессина. Можно предположить, что в ряде случаев, в том числе в опухолях, центральная нейрогормональная регуляция синхронизирует в тканях пролиферативный ответ на вазопрессин (Garona et al, 2015). Активная пролиферация тканей всегда сопровождается реорганизацией локальной системы кровоснабжения (Maharaj et al, 2006).…”
Section: активация тромбоцитов и эндотелиоцитовunclassified